The Growth of 3T3 Fibroblasts on PHB, PLA and PHB/PLA Blend Films at Different Stages of Their Biodegradation In Vitro; Polymers; Vol. 13, iss. 1 - Zhuikov V. A. Vsevolod; Akoulina E. A. Elizaveta; Chesnokova D. V. Dariana; Wenhao You; Makhina T. K. Tatiana; Demyanova I. V. Irina; Zhuikova Yu. V. Yuliya; Voinova V. V. Vera; Belishev N. V. Nikita; Surmenev R. A. Roman Anatolievich; Surmeneva M. A. Maria Alexandrovna; Bonartseva G. A. Garina; et al. (2021, 2021)
Title screen